MENGEMBANGKAN PEMAHAMAN KONSTITUSI MELALUI PEMBELAJARAN TENTANG LEMBAGA NEGARA DI PENDIDIKAN TINGGI - Satio Darma (EDU RESEARCH, 2024)
This study aims to analyze the effectiveness of case-based and project-based learning methods in improving students' understanding of state institutions and the constitution in higher education. Learning methods based on case studies and projects have proven effective in enhancing students' critical, analytical, and practical skills in understanding complex constitutional concepts. Additionally, this study discusses the factors that influence students' understanding of constitutional material and the role of state institutions, such as teaching quality, student motivation, academic background, and students' active involvement in learning. The study's findings indicate that a combination of interactive learning methods, along with individual student factors, can enhance their understanding of topics related to the constitution and state institutions. Therefore, it is essential for higher education institutions to adopt more active and contextual learning methods to enrich students' understanding of these topics.